Truth about Rape Myths: Understanding the Effects of Sexual Violence and Date Rape Attitudes on Rape Myths Acceptance in Ghana - Boateng, Francis Danso; Oti-Boadi, Mabel; Darko, Isaac Nortey (International Journal of Criminology and Sociology, 2024)
Purpose: Rape myths acceptance is a global phenomenon with dire consequences on how sexual assault victims are perceived and treated. People who hold strong sexual violence beliefs tend to blame the victims for their victimizations while praising the offenders. It has widely been acknowledged that such attitudes hinder crime reporting while promoting violence in society. The main purpose of the current study was to examine the factors that influence rape myths acceptance among students in Ghana. Method: Data for the study was collected from students attending one of the largest universities in the country between 2021 and 2022. Results: Our results revealed that sexual violence experience, college date rape attitudes, age, degree program, and ethnicity influenced rape myths acceptance among students. Conclusion: Based on the findings, we recommend that colleges should create a conducive environment for victims of sexual violence whereby educating students about the harmful effects of rape myths acceptance.